Specifying a programming exercises evaluation service on the e-Framework - Leal, José Paulo (2014)
The e-Framework is arguably the most prominent e-learning framework currently in use. For this reason it was selected as basis for modelling a programming exercises evaluation service. The purpose of this type of evaluator is to mark and grade exercises in computer programming courses and in programming contests. By exposing its functions as services a programming exercise evaluator is able to participate in business processes integrating different system types, such as Programming Contest Management Systems, Learning Management Systems, Integrated Development Environments and Learning Object Repositories. This paper formalizes the approaches to be used in the implementation of a programming exercise evaluator as a service on the e-Framework.